2020
DOI: 10.1097/md.0000000000023421
|View full text |Cite
|
Sign up to set email alerts
|

Auricular therapy improves gastrointestinal function in patients with gynecological laparoscopic surgery

Abstract: Background: Gynecological laparoscopic surgery is the main method to treat gynecological diseases, but postoperative gastrointestinal reactions are more common in patients. Auricular therapy, as a characteristic therapy of Traditional Chinese Medicine, can improve gastrointestinal symptoms such as nausea and vomiting by stimulating the conduction of acupoints through the nervous system on internal organs, but there are studies questioning the efficacy of auricular therapy. Therefore, the purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Many scholars at home and abroad have conducted in-depth research on the influencing factors of gastrointestinal function recovery. For example, Bozkurt Koseoglu et al found through research that the ERAS concept can not only speed up the recovery of patients after surgery but also improve patients' recovery and quality of life [ 5 ]; Cao et al found that moxibustion is better than Western medicine nursing treatment [ 6 ]; Hu et al found through experiments that acupuncture and moxibustion are helpful for the early recovery of gastrointestinal function after surgery [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars at home and abroad have conducted in-depth research on the influencing factors of gastrointestinal function recovery. For example, Bozkurt Koseoglu et al found through research that the ERAS concept can not only speed up the recovery of patients after surgery but also improve patients' recovery and quality of life [ 5 ]; Cao et al found that moxibustion is better than Western medicine nursing treatment [ 6 ]; Hu et al found through experiments that acupuncture and moxibustion are helpful for the early recovery of gastrointestinal function after surgery [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…How to make the perioperative period of the sleeve stomach smoother for patients and improve patient satisfaction in hospital is now a growing concern. And auricular pressure as a noninvasive, fast-acting, easy-to-use and inexpensive treatment modality has been used after laparoscopic surgery, mainly gynaecological laparoscopy, to relieve PONV [25] .…”
Section: Discussionmentioning
confidence: 99%